2015
DOI: 10.4315/0362-028x.jfp-15-087
|View full text |Cite
|
Sign up to set email alerts
|

Adherence Reduction of and Strains to HEp-2 Cells by Mannan Oligosaccharides and a High-Molecular-Weight Component of Cranberry Extract

Abstract: Campylobacter infections are a leading cause of human bacterial gastroenteritis in the United States and are a major cause of diarrheal disease throughout the world. Colonization and subsequent infection and invasion of Campylobacter require that the bacteria adhere to the surface of host cells. Agents that inhibit adherence could be used prophylactically to reduce Campylobacter carriage and infection. Mannan oligosaccharides (MOS) have been used as a feed supplement in livestock animals to improve performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 71 publications
2
8
0
Order By: Relevance
“…This result agrees with our previous reports ( Upadhyay et al., 2017 ) and others ( Van Alphen et al., 2012 ), which also showed the antiadhesion property of carvacrol on human epithelial cells. Similar results have also been reported with berries ( Salaheen et al., 2014 ), cranberry extract ( Ramirez-Hernandez et al., 2015 ), Alpinia katsumadai extracts ( Šikić Pogačar et al., 2015 ), grape extract ( Klančnik et al., 2017 ), thyme extracts ( Šikić Pogačar et al., 2016 ), herbal extracts ( Bensch et al., 2011 ), β-resorcylic acid ( Wagle et al., 2017a ), and resveratrol ( Klančnik et al., 2017 ). Adding to the knowledge of these studies, our data suggest that carvacrol exerts antiadhesion properties to primary chicken enterocytes at chicken body temperature (42°C).…”
Section: Discussionsupporting
confidence: 85%
“…This result agrees with our previous reports ( Upadhyay et al., 2017 ) and others ( Van Alphen et al., 2012 ), which also showed the antiadhesion property of carvacrol on human epithelial cells. Similar results have also been reported with berries ( Salaheen et al., 2014 ), cranberry extract ( Ramirez-Hernandez et al., 2015 ), Alpinia katsumadai extracts ( Šikić Pogačar et al., 2015 ), grape extract ( Klančnik et al., 2017 ), thyme extracts ( Šikić Pogačar et al., 2016 ), herbal extracts ( Bensch et al., 2011 ), β-resorcylic acid ( Wagle et al., 2017a ), and resveratrol ( Klančnik et al., 2017 ). Adding to the knowledge of these studies, our data suggest that carvacrol exerts antiadhesion properties to primary chicken enterocytes at chicken body temperature (42°C).…”
Section: Discussionsupporting
confidence: 85%
“…Zhao and Shah () have reported that tea and soybean extracts were found to inhibit adherence of the foodborne pathogens to Caco‐2 cells. In another study, reduction in the adherence ability of C. jejuni and C. coli isolates to HEp‐2 cells were reported upon treatment with mannan oligosaccharides and fraction of cranberry extract (Ramirez‐Hernandez, Rupnow, & Hutkins, ). In the present work, however, upon exposure of Caco‐2 cells with Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…As mannose glycosides have a significantly higher affinity for the Klebsiella pneumonia , it is likely that FimH structure varies between species and are also presented differently [ 161 ]. This difference is also reflected in superior Escherichia coli specificity for mono-or trimannose moieties [ 162 , 163 ]. Furthermore, significant reduction in the adherence of Campylobacter jejuni and coli to human epithelial cells was observed in the presence of MOS [ 163 ].…”
Section: Mannan-oligosaccharidesmentioning
confidence: 99%
“…This difference is also reflected in superior Escherichia coli specificity for mono-or trimannose moieties [ 162 , 163 ]. Furthermore, significant reduction in the adherence of Campylobacter jejuni and coli to human epithelial cells was observed in the presence of MOS [ 163 ]. An overview of anti-adhesion activities is shown in Table 6 .…”
Section: Mannan-oligosaccharidesmentioning
confidence: 99%